(untitled) (Revista Rupturas, 2024)
The objective of this article is to analyze the factors associated with youth school permanence in Costa Rican public daytime high school students, during the period 2015 - 2019. A quantitative approach study was conducted with a retrospective longitudinal design using cohort analysis to reconstruct the educational trajectories of two groups of students: those who remain and those who interrupt their studies. Among the main results and conclusions is that there is a greater disadvantage among young people who interrupted their studies in most of the indicators analyzed, with greater relative differences in socioeconomic factors and educational trajectories. Educational inequality is an expression of a previous condition: social inequality, which is why it is necessary to strengthen social policies that tend to reduce inequalities of origin.